Staphylococcus lugdunensis: an unusual cause of relapsing hematogenous septic arthritis of a native knee. Case report and review of the literature - Wery, Alexandre-Raphael; Taghavi, Maxime; Nortier, Joelle; Mahadeb, Bhavna; Raftakis, Ioannis; Maillart, Evelyne; Clevenbergh, Philippe (Frontiers in Medicine, 2024)
Staphylococcus lugdunensis is a facultatively anaerobic gram-positive cocci of the coagulasenegative staphylococcus (CoNS) species. Initially considered as commensal, S. lugdunensis has been found to be responsible for a wide range of disseminated infections in humans (bacteriemia, foreign-body infection, endocarditis, arthritis, osteomyelitis, …) thereby often compared to Staphylococcus aureus in terms of virulence behavior. We present the case of a 62-year-old woman with end-stage renal disease, undergoing hemodialysis through an arteriovenous fistula (AVF) of the left forearm. She was diagnosed with S. lugdunensis bacteriemia and secondary native-knee septic arthritis. Endocarditis was ruled out and the patient evolved well with a 6-week course of IV cefazolin. Four months later, she consulted the rheumatology department with a recurrent right knee arthritis. Cultures came back positive for an identical multi-sensitive S. lugdunensis. Endocarditis was ruled out and full body 18F-FDG PET-CT showed no secondary location but a focal hypermetabolic activity in the left forearm fistula area. AVF Doppler showed no sign of collection nor thrombophlebitis around the fistula. We concluded in an infection of the fistula due to repeated punctures (recurrent cannulation) as entry point. She was treated with a 12week oral combination of ciprofloxacin and trimethoprim-sulfamethoxazole, and her symptoms have not returned since. S. lugdunensis commonly causes prosthetic and arthroscopy-related joint infections. As native-joint septic arthritis is unusual, we conducted a review of the literature and discuss the burden of disseminated S. lugdunensis infections among dialysis patients.